Investigation of Learning Activity In Secondary School - Maison Maison; Astalini Astalini; Dwi Agus Kurniawan; Darmaji Darmaji; Nur Ika Sandi Pratiwi (Jurnal Pendidikan Indonesia, 2021)
This study aims to examine the activeness of student learning towards science subjects in junior high school. The research method used was a mixed research method with an explanatory design. The subjects were students of junior high school amounted to 148 students. The analysis of data using statistical techniques descriptive for quantitative data and analysis Miles Huberman for qualitative data. The results of the five indicators show that students are categorized as having good learning activeness on the indicator "High Curiosity (45,3%)" "Dare to Take Risks (73,7 %) ". "Wanted for New Experiences (55,4 %)". And "Proactive (57,4 %)". Then, students are categorized as having sufficient learning activeness on the indicator "Never Give Up (45,3 %)". The high percentage of the five indicators is supported by the results of interviews stating that students have a high curiosity seen from students who is actively asking questions and also not only rely on the material provided by the teacher, students have dared to make their own decisions and dare to face the problems given by the teacher without fear of being wrong, students are enthusiastic in conducting experiments or experiments because through theoretical experiments can be easier to understand and through experiments learning experiences can be obtained directly, and students are always looking for opportunities to learn and involved in learning activities, and students have a high enthusiasm for learning science but they are not confident in their abilities.